Membaca Tanda Zaman melalui Bencana Alam di Sumatera: Sebuah Refleksi Ekologis - Thersiani Bheka; Monica Innanda Chiaralazzo; Intansakti Pius X (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to reflect on the theological meaning of natural disasters in Sumatra (Aceh, Simeulue, Padang) from an ecological perspective. Although Sumatra is geologically prone to earthquakes and tectonic activities due to its location on the Pacific Ring of Fire, hydrometeorological disasters such as floods and landslides are exacerbated by human actions, including deforestation, watershed degradation, and uncontrolled land conversion. This research employs a qualitative-descriptive approach using library research and a theological-reflective method. Primary sources include Sacred Scripture, Church documents (Laudato Si', Gaudium et Spes, General Directory for Catechesis), and relevant ecological theology literature. The findings indicate that natural disasters in Sumatra can be interpreted as "signs of the times" revealing both ecological and moral crises. Disasters are not divine punishment but consequences of humanity's misuse of freedom in managing creation. Ecological conversion is urgently needed at personal, social, and structural levels. Within the catechetical framework, disaster experiences become "texts of life" that guide the faithful toward mature faith expressed in lifestyle changes, solidarity, and responsibility for our common home.